Key informant perspectives on 3 am last drinks legislation in Queensland, Australia. (27th October 2022) - Miller, Peter G.; Farmer, Clare; Robertson, Narelle; Coomber, Kerri; Curtis, Ashlee; Baldwin, Ryan; Patafio, Brittany; Ferris, Jason; Puljevic, Cheneal; Taylor, Nicholas; de Andrade, Dominique
Abstract: Introduction: The objective of this study was to explore key informant attitudes towards the 'Last Drinks at 3am' legislation in Safe Night Precincts in Queensland, Australia. Method: Sixty‐six interviews were conducted with a range of stakeholders including licensees, law enforcement and frontline health professionals. Interviews were semi‐structured and analysed using thematic analysis. Key informants responded to questions regarding their experiences of, and opinions about, the last drinks legislation. Results: Key informants reported a range of experiences around the impact of last drinks restrictions, including reduced staffing costs and patron‐related problems within licensed venues. While some venues reported that their businesses lost money, others reported no change in income or that they changed their business model to compensate. Law enforcement and health professionals reported a range of benefits including reduced alcohol‐related anti‐social behaviour, drunkenness and injury. Conclusions: The majority of key informants reported that the last drinks legislation reduced harm, while having minimal detrimental impact on business.